1988
DOI: 10.2172/6574504
|View full text |Cite
|
Sign up to set email alerts
|

Geohydrologic characterization of the area surrounding the 183-H Solar Evaporation Basins

Abstract: , the Pacific Northwest Laboratory has been conducting a geohydrologic in Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 3 publications
2
25
0
Order By: Relevance
“…1987a,b,c,d;1988b,c,d;Fruland, Bates, and Lundgren 1989) contain information on the progress made and the data obtained by the Resource Conservation and Recovery Act (RCRA) GroundWater Quality Assessment Program for the 183-H Solar Evaporation Basins during the period May I, 1986through September 30, 1988. In addition, a final hydrogeologic characterization report has been published (Liikala et al 1988). A Final Status Post-Closure Permit Application for this facility was submitted to the Washington State Department of Ecology in June 1988 (WHC !988a).…”
Section: Sampling System Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…1987a,b,c,d;1988b,c,d;Fruland, Bates, and Lundgren 1989) contain information on the progress made and the data obtained by the Resource Conservation and Recovery Act (RCRA) GroundWater Quality Assessment Program for the 183-H Solar Evaporation Basins during the period May I, 1986through September 30, 1988. In addition, a final hydrogeologic characterization report has been published (Liikala et al 1988). A Final Status Post-Closure Permit Application for this facility was submitted to the Washington State Department of Ecology in June 1988 (WHC !988a).…”
Section: Sampling System Statusmentioning
confidence: 99%
“…Well locations are shown in Figure 3.1. A water-table map is included in Liikala et al (1988) and will be included in the next quarterly report.…”
Section: Hydrogeologic Characterizationmentioning
confidence: 99%
“…The 183-H Solar Evaporation Basins consist of four concrete basins in the 100-H Area (see Figures 1.1 and 3.1) that were used for solar evaporation and storage of aqueous chemical wastes from nuclear fuel processing operations elsewhere on the Hanford Site (Liikala et al 1988). The wastes discharged to the basins consisted primarily of nitric, sulfuric, and hyd(ofluoric acids, contaminated by heavy metals and radionuclides, and neutralized by sodium hydroxide.…”
Section: -H Solar Evaporation Basins S H Hallmentioning
confidence: 99%
“…Gross alpha, gross beta, and technetium-99 exceed the 900-pCi/L standard in EPA (1976). Liikala et al (1988) have shown that the apparent shape and extent of the contaminant plume extending from the 183-H basins is highly dependent upon river stage. At high river stage (see Figure 3.5), there is a temporary gradient reversal, although the net annual flow is towards the Columbia River.…”
Section: Water Chemistry Datamentioning
confidence: 99%
“…Hydraulic property data used in the development of the prior model were obtained from the results of hydraulic tests documented in Bierschenk (1959), Kipp and Mud (1973), Deju (1974), Lindberg and Bond (1979), Graham et al (1981), DOE (1988a), Liikala and Aaberg (1988), Thorne and Newcomer (1992), Peterson (1992), Connelly et al (1992aConnelly et al ( , 1992b, Swanson (1992), Thorne et al (1993), Connelly (1994), and Swanson (1994). Information was also obtained from new tests and tests that were previously undocumented.…”
Section: Introductionmentioning
confidence: 99%